Relationship between Neutrophil-Lymphocyte Ratio (NLR) and Self-Esteem in Patients with Borderline Personality Disorder - Uminah; Widodo Sarjana AS; Muflihatunnaimah; Natalia Dewi Wardani (Scientia Psychiatrica, 2024)
Background: Borderline personality disorder (BPD) is a personality disorder that has low self-esteem, unstable emotions, high rejection, and is reactive to everyday interpersonal stress. The involvement of inflammatory factors in BPD has been widely reported by researchers. NLR is a specific inflammatory mediator in the adaptive immune response that can be examined through inexpensive and fast hematology tests. NLR is expected to be used as a marker of self-esteem in individuals with BPD. The study aimed to determine the relationship between NLR and self-esteem in patients with BPD. Methods: This is a quantitative study with a cross-sectional design. The total sample is 37 respondents who have been diagnosed with BPD from several hospitals in Semarang. Collection data use questionnaire RSES and blood sampling for NLR examination. Results: From 37 respondents, 27 (73.0%) subjects had low self-esteem, and 10 (27.0) subjects had high self-esteem. We found that the sensitivity of NLR was 50.00%, specificity 48.15%, positive predictive value 26.32%, negative predictive value 27.03%, and accuracy 48.65%. Area under curve (AUC) 0,537 and correlation cut off point NLR to self-esteem is no significant relationship because the p-value is 0,605 with RP 0.93(0,22-3,96) (95% CI). Conclusion: NLR cannot be used as a marker of high or low self-esteem in individuals with BPD.